Implementation of High-Sensitivity Cardiac Troponin: Challenges from the International Experience - Howell, Stacey J. (Crit Pathw Cardiol, 2018)
BACKGROUND: Implementation of the newly approved high-sensitivity cardiac troponin (hs-cTn) in the United States presents a challenge for clinical practice. Sex-specific cut-offs, clinical protocols, and workflows will likely require modifications before implementation. METHODS: We conducted a cross-sectional survey of international physicians and laboratorians already utilizing hs-cTn for the evaluation of acute myocardial infarction (AMI). RESULTS: Twenty-two of 54 (41%) eligible participants completed the survey, representing nine countries and 18 hospitals. All reported successful hs-cTn implementation and diagnostic utility (mean 8.6+1.2 out of 10 for best implementation). The major perceived benefit was more rapid evaluation of AMI (14/19, 74%) and the most frequently cited limitation was an increase in the number of measurable hs-cTn values that required further evaluation (8/18, 44%). Institutions using the hs-cTnI assay favored sex-specific cut-offs (5/6, 83%) while institutions employing the hs-cTnT assay favored a combined cut-off (12/12, 100%). Timing of serial hs-cTn measurements varied, with 0–3 hours (8/17, 47%) most frequent, followed by 0–2 hours (4/17, 24%), 0–1 hour (3/17, 18%), and other (2/17, 12%). CONCLUSIONS: Our survey of hs-cTn implementation at international institutions reveals satisfaction with new assays but reflects important variations in clinical practice. The use of sex-specific vs combined cut-offs and timing of serial hs-cTn measurements varies across institutions and are subjects that US centers must define without consensus from international practices.